Outdoor Smoke-Free Policies in Maine - Harris, David; Roy, Suzanne; Mayberry, Sarah (Maine Policy Review, 2012)
Incontrovertible evidence of the deadly impacts from both direct tobacco use and environmental exposure to tobacco smoke has led to the institution of smoking bans, first in indoor venues and, more recently, in some outdoor area. This article reviews the science behind smoking bans as well as the history and policy implications of smoking bans with an emphasis on the experience in Maine. As examples we focus on recent outdoor smoking bans in South Portland (parks and beaches) and smoke-free campus rules at a Maine hospital (Franklin Memorial Hospital) and a part of the University of Maine system (University of Southern Maine). Our conclusions highlight the interconnections among federal, state, municipal, and public institutional efforts to limit smoking and suggest pathways by which smoke-free areas can be expanded in Maine and elsewhere.